(untitled) (African Journal of Biomedical Research, 2023)
Consumption of sugar sweetened beverages has been on the increase among children and adolescents and has been implicated in the overweight and obesity. The study was designed to assess the relationship between beverage consumption and body mass index among adolescents. The study was a cross-sectional descriptive study conducted among 400 adolescents, 10-19 years. A structured questionnaire was used to collect information on the personal and socio-economic characteristics and nutrition knowledge of respondents. Beverage consumption pattern was assessed using a semi-quantitative food frequency questionnaire. Physical activity was measured using the WHO global-activity questionnaire. Descriptive statistics were used for analysis and Chi-square test and multi nominal logistic regression analysis were used for identifying factors associated with beverage consumption. The prevalence of underweight, overweight and obesity were 18.5%, 6.8% and 2.2% respectively. Carbonated and fruit juice with sugar drinks were the most frequently consumed beverage with an average intake of 500ml per portion among the consumers. However, milk consumption was rather low (28ml per portion). Only 4.3% had poor nutrition knowledge and 10% had low physical activity level. Respondents in senior classes had significantly higher nutrition knowledge than those in junior classes (p= 0.001). Also, the male adolescents were significantly more physically active than their female counterpart (p=0.012). In addition, consumption and quantity of carbonated drinks was significantly associated with BMI-for-age (p<0.05). The logistic regression analysis shows statistical significant difference (p=0.033) in the beverage consumption pattern of respondents in the junior and senior secondary class. The odds (OR = 1.529) of consumption of fruit juices with sugar increases from 125- 350mls (P=0.279, 95%CI:0.709 – 3.294). Despite higher nutrition knowledge among the respondents in the senior secondary class, beverage consumption was significantly higher among this group.